2018
DOI: 10.5194/bg-15-6519-2018
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of methanogens over methanotrophs in rewetted fens characterized by high methane emissions

Abstract: Abstract. The rewetting of drained peatlands alters peat geochemistry and often leads to sustained elevated methane emission. Although this methane is produced entirely by microbial activity, the distribution and abundance of methane-cycling microbes in rewetted peatlands, especially in fens, is rarely described. In this study, we compare the community composition and abundance of methane-cycling microbes in relation to peat porewater geochemistry in two rewetted fens in northeastern Germany, a coastal brackis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 71 publications
2
53
2
Order By: Relevance
“…Methanoperedens) which reduce CH4 by the reverse methanogenic pathway [20] were detected in the water-covered fen Alderwet. Although we did not find a clear correlation between methanogen and methanotroph abundance (see [16] for similar findings), we did find a strong distinction of anaerobic and aerobic methanotrophs depending on water content and therefore oxygen availability, between sites and depths.…”
Section: Interactions Between Methanogens Methanotrophs and Sulfate contrasting
confidence: 38%
See 2 more Smart Citations
“…Methanoperedens) which reduce CH4 by the reverse methanogenic pathway [20] were detected in the water-covered fen Alderwet. Although we did not find a clear correlation between methanogen and methanotroph abundance (see [16] for similar findings), we did find a strong distinction of anaerobic and aerobic methanotrophs depending on water content and therefore oxygen availability, between sites and depths.…”
Section: Interactions Between Methanogens Methanotrophs and Sulfate contrasting
confidence: 38%
“…Rewetting is a proven strategy to protect the large SOC stocks; however, it can also lead to increased emissions of the potent GHG CH4 and to the release of dissolved organic matter (DOM). While effects of peatland rewetting on GHG and DOM fluxes are comparably well studied [11][12][13][14][15], the impact on the peat microbiota, the primary driver of GHG production and emissions, is poorly understood, since it has been not well studied in temperate fens (see an exception in [16]). The major players in soil organic matter (SOM) decomposition in peat soils are microorganisms of the bacterial, archaeal and eukaryotic (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), due to the high amount of sulfate reducers in CW which is regularly flooded with sea water. The higher abundance of methanogens in rewetted sites seems to be the main reason for the increase of CH 4 production and thus potentially emission after rewetting [36]. It has been shown that CH 4 dominated the balances of annual greenhouse gases in decades after rewetting a bog in Lower Saxony [16].…”
Section: Discussionmentioning
confidence: 99%
“…Peatlands along the coastal margins are also a major source of DOC to coastal and shelf areas (Freeman et al 2001; Mulholland 2003). Currently, the majority of experimental studies considering carbon transformation processes from wetland soil focus on onshore processes (Kalbitz et al 2000; Chambers et al 2011; Wen et al 2018; Säurich et al 2019). A number of experimental approaches have identified the ionic strength of the advective pore water as an important factor controlling DOC concentrations and mobilization, where increasing ionic strength results in decreasing DOC release from organic soils and vice versa (Tipping and Hurley 1988; Limpens et al 2008; Tiemeyer et al 2017).…”
mentioning
confidence: 99%